2014
DOI: 10.1007/s11999-013-3319-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acetabular Anterior Coverage After Salter Osteotomy and Pemberton Acetabuloplasty: A Long-term Followup

Abstract: Background The Salter osteotomy and Pemberton acetabuloplasty are common procedures for a deficient acetabulum in patients with developmental dysplasia of the hip. However, the degree of increasing retroversion and anterior acetabular coverage of these two procedures remains unanswered. Questions/purposes The purpose of this study is to show the change in anterior coverage and relevant parameters in measuring pain and function among patients who have undergone either a Salter osteotomy or Pemberton acetabulopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 12 publications
1
35
0
3
Order By: Relevance
“…This observation contradicts Reynolds et al's proposal [16] that all the symptomatic hips with acetabular retroversion have a positive anterior impingement. The comparison study between Salter and Pemberton osteotomy by Wang et al [24] showed no patient displayed a positive anterior impingement sign in the patients after Salter osteotomy compared with 11% of patients showing a positive sign after Pemberton osteotomy. Their study showed less frequency of clinical sign of FAI after Salter osteotomy and was consistent with ours.…”
Section: Discussionmentioning
confidence: 98%
“…This observation contradicts Reynolds et al's proposal [16] that all the symptomatic hips with acetabular retroversion have a positive anterior impingement. The comparison study between Salter and Pemberton osteotomy by Wang et al [24] showed no patient displayed a positive anterior impingement sign in the patients after Salter osteotomy compared with 11% of patients showing a positive sign after Pemberton osteotomy. Their study showed less frequency of clinical sign of FAI after Salter osteotomy and was consistent with ours.…”
Section: Discussionmentioning
confidence: 98%
“…Pemberton pericapsular osteotomy (PPO) was defined by Pemberton 6 in 1965 and is widely recognized as a safe and effective procedure both in terms of clinical and radiographic outcomes in children. 7 11 However, there are reports of residual gait deviations in patients previously treated with PPO for DDH that decreased function and made revision surgery challenging. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…In one study comparing long-term results of those two osteotomies, it suggested that by modifying the acetabular shape, the Pemberton osteotomy may result in an increase in anterior acetabular coverage. This in term may increase the risk of impingement [10]. Leg length discrepancy with longer leg at pathology side may be caused by coxa valga due to Kalamchi type II osteonecrosis of femoral head or trans-iliac lengthening of the pelvis [6].…”
Section: Change Of Hip Joint Anatomymentioning
confidence: 99%